A Review on Test Automation for Test Cases Generation using NLP Techniques - Dr. Ajay Roy, Srinivas Perala, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the process of product development, stakeholders and top management summarize the concept and document the requirements in natural language. These ideas and descriptions documented as software requirements by the technical department. Developers develop software following this software requirement document. For testing this developed software, they derive test cases from natural language requirements and then do the testing process to find the bugs. This process involves understanding requirements and derives test cases that are used to understand by developers and testers. Due to increasing the advanced features, deriving the test cases is monotonous and takes more time. This research article shows a method to automate this process which is deriving test cases from requirements using NLP algorithms. This approach useful to reduce the time and cost of software development.